3T MRI evaluation of regional catecholamine-producing tumor-induced myocardial injury. Issue 5 (May 2019) - Higuchi, Satoshi; Ota, Hideki; Ueda, Takuya; Tezuka, Yuta; Omata, Kei; Ono, Yoshikiyo; Morimoto, Ryo; Kudo, Masataka; Satoh, Fumitoshi; Takase, Kei
Abstract : Objective: Regional differences in cardiac magnetic resonance, which can reveal catecholamine-induced myocardial injury in patients with pheochromocytoma, have not yet been assessed using 3T magnetic resonance imaging. We evaluated these differences using myocardial T1-mapping and strain analysis. Design and Methods: We retrospectively reviewed 16 patients newly diagnosed with catecholamine-producing tumors (CPT group) and 16 patients with essential hypertension (EH group), who underwent cardiac magnetic resonance imaging between May 2016 and March 2018. We acquired 3T magnetic resonance cine and native T1-mapping images and performed feature-tracking-based strain analysis in the former. Results: Global cardiac function, morphology, global strain and peak strain rate were similar, but end-diastolic wall thickness differed between groups (CPT vs EH: 10.5 ± 1.7 vs 12.6 ± 2.8 mm; P < 0.05). Basal, but not apical, circumferential strain was significantly higher in the CPT than the EH group (19.4 ± 3.2 vs 16.8 ± 3.6 %; P < 0.05). Native T1 values were significantly higher in CPT than in EH patients, in both the basal septum (1307 ± 48 vs 1241 ± 45 ms; P < 0.01) and the apical septum (1377 ± 59 vs 1265 ± 58 ms; P < 0.01) mid-walls. In the CPT, but not in the EH group, native T1 values in the apical wall were significantly higher than those in the basal wall ( P < 0.01). Conclusion: 3T magnetic resonance-based T1-mapping can sensitively detect subclinical catecholamine-induced myocardial injury; the influence of catecholamines may be greater in the apical than in the basal wall.